Enhanced corrosion resistance of Zn–Cu–Ti alloy with addition of Cu–Ti amorphous ribbons in 3.5% NaCl solution. Issue 7 (8th February 2021) - Ni, Ya; Wu, Guoguang
Abstract: In the present study, Zn–0.3Cu–0.3Ti alloy (sample I) was fabricated by a simple low‐temperature melting method using Cu–50Ti amorphous alloy ribbons for corrosion in 3.5% NaCl solution. As a comparison, crystalline Cu–50Ti master alloy was used to prepare Zn–0.3Cu–0.3Ti alloy (sample II). Sample I comprising Zn, TiZn3, and TiZn15 phases exhibits an equiaxed microstructure with subgrain structure. Large TiZn3 particles show cluster feature, whereas intermittent small TiZn15 particles exist at grain boundaries and subgrain boundaries. In sample II, the Zn matrix with typical dendritic microstructure is observed and no large particles are found. Compared with sample II, sample I shows lower weight gain and corrosion current density and a higher slope of cathode polarization curve. The weight gain for sample I is only 0.59 mg·cm −2, but for sample II, this value reaches 0.70 mg·cm −2 . After 8 days of corrosion, corrosion products are mainly Zn5 (OH)8 Cl·H2 O and ZnO, showing loose particle shape. As corrosion time increases from 2 days to 8 days, corrosion layer thickness increases from about 15 to 24 μm for sample 1. Abstract : Zn–0.3Cu–0.3Ti alloy (sample I) was fabricated by a simple low‐temperature melting method using Cu–50Ti amorphous alloy ribbons for corrosion in 3.5% NaCl solution. As a comparison, crystalline Cu–50Ti master alloy was used to prepare Zn–0.3Cu–0.3Ti alloy (sample II). Compared with sample II, sample I shows lower weight gain and corrosion current density and a higher slope of cathode polarization curve.